PDGF Receptor Alpha+ Mesoderm Contributes to Endothelial and Hematopoietic Cells in Mice. Issue 3 (13th February 2013) - Ding, Guo; Tanaka, Yosuke; Hayashi, Misato; Nishikawa, Shin‐Ichi; Kataoka, Hiroshi
<x xml:space="preserve">Abstract</x> Background: Early mesoderm can be classified into Flk‐1+ or PDGF receptor alpha (PDGFRα)+ population, grossly representing lateral and paraxial mesoderm, respectively. It has been demonstrated that all endothelial (EC) and hematopoietic (HPC) cells are derived from Flk‐1+ cells. Although PDGFRα+ cells give rise to ECs/HPCs in in vitro ES differentiation, whether PDGFRα+ population can become hemato‐endothelial lineages has not been proved in mouse embryos. Results: Using PDGFRαMerCreMer mice, PDGFRα+ early mesoderm was shown to contribute to endothelial cells including hemogenic ECs, fetal liver B lymphocytes, and Lin‐Kit+Sca‐1+ (KSL) cells. Contribution of PDGFRα+ mesoderm into ECs and HPCs was limited until E8.5, indicating that PDGFRα+/Flk‐1+ population that exists until E8.5 may be the source for hemato‐endothelial lineages from PDGFRα+ population. The functional significance of PDGFRα+ mesoderm in vascular development and hematopoiesis was confirmed by genetic deletion of Etv2 or restoration of Runx1 in PDGFRα+ cells. Etv2 deletion and Runx1 restoration in PDGFRα+ cells resulted in abnormal vascular remodeling and rescue of fetal liver CD45+ and Lin‐Kit+Sca‐1+ (KSL) cells, respectively. Conclusions: Endothelial and hematopoietic cells can be derived from PDGFRα+ early mesoderm in mice. PDGFRα+ mesoderm is functionally significant in vascular development and hematopoiesis from phenotype analysis of genetically modified embryos. Developmental Dynamics 242:254–268, 2013. © 2013 Wiley Periodicals, Inc.